Firefighter Pete - Dean, James, 1957- (New York, NY : HarperFestival, an imprint of HarperCollinsPublishers, 2018)
Pete the cat takes a trip to the firehouse, where he tries on a firefighter's gear, takes a ride in a fire engine, and helps save Grumpy Toad from a burning building.
Keywords: Cats -- Fiction; Fire fighters -- Fiction; Fire extinction -- Fiction; Cats -- Juvenile fiction; Fire fighters -- Juvenile fiction; Fire extinction -- Juvenile fiction